2017
DOI: 10.11124/jbisrir-2017-003439
|View full text |Cite
|
Sign up to set email alerts
|

eHealth interventions for parents in neonatal intensive care units: a systematic review

Abstract: While heterogeneity across studies precluded meta-analysis, consistent trends across all studies examining parental acceptance of eHealth interventions indicate that parents are willing to accept eHealth interventions as part of their neonatal intensive care, suggesting that the incorporation and evaluation of eHealth interventions in the neonatal intensive care unit setting is warranted. Further high quality studies are needed with larger sample sizes to detect changes in outcomes. As eHealth intervention stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 38 publications
0
50
0
Order By: Relevance
“…Alderdice et al recently published a study that reviewed potential websites that families found useful after discharge home [55]. A recent meta-analysis suggested families have generally accepted mHealth interventions while in the NICU [56] which may be translated to the outpatient settings as well. Other studies have supported the use of webcams in the NICU and videoconferencing with families at home [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…Alderdice et al recently published a study that reviewed potential websites that families found useful after discharge home [55]. A recent meta-analysis suggested families have generally accepted mHealth interventions while in the NICU [56] which may be translated to the outpatient settings as well. Other studies have supported the use of webcams in the NICU and videoconferencing with families at home [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…While convenient, information on the Internet is often unregulated and may be inaccurate, making it difficult for parents to evaluate the quality and relevance of the information (D'Alessandro & Dosa, 2001;Nicholl et al, 2017). In a systematic review on eHealth interventions for parents in neonatal intensive care, Dol et al (2017) reported that 84% of parents found information on the Internet harder to understand than information provided by clinicians. Moreover, 73% of parents reported that the information they found online was inadequate (Dol et al, 2017).…”
Section: Education and Information Methodsmentioning
confidence: 99%
“…Additionally, the information needs of parents with children with chronic illnesses may change over time as they become experts in their child's day-to-day management (Hummelinck & Pollock, 2006). With unmet informational needs, families increasingly seek out other sources of information, such as the Internet, to fill gaps in knowledge; however, parents often become frustrated by the lack of reliable and trustworthy informational resources (Dol et al, 2017;Lewis et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Provide telehealth support after discharge [150][151][152][153][154][155] 36. Use technology and social media to support families [156][157][158][159][160][161][162][163][164][165] 37. Facilitate access to all necessary clinical specialists after discharge 121,134 38.…”
Section: Addendummentioning
confidence: 99%